Platinum-group element concentrations in base-metal sulphides from the Platreef, Mogalakwena Platinum Mine, Bushveld Complex, South Africa - Klemd, Reiner; Junge, Malte; Oberthür, Thomas; Herderich, Tobias; Schouwstra, R. P.; Roberts, Jaques (South African Journal of Geology, 2016)
Base-metal sulphides (BMS) are important host minerals for platinum-group elements (PGE) in orthomagmatic Ni-Cu-PGE deposits. The PGE distribution and concentration in the BMS provide important genetic, exploration and mineral processing information. Therefore, detailed mineralogical work and an in situ laser ablation inductively-coupled plasma mass spectrometry (LA-ICP-MS) analysis of trace elements were conducted on the BMS of mineralised samples from the Overysel and Sandsloot localities of the Mogalakwena Platinum Mine. These localities access the Platreef of the northern Bushveld Complex. Platinum-group element enrichment trends in the BMS are similar in the Overysel and Sandsloot samples, although the overall PGE concentrations in the Overysel BMS are lower than those in the Sandsloot BMS. A general decoupling of the PGE from the BMS due to fluid activity, as advocated by other authors for the Sandsloot reef lithologies, was not observed in the samples studied. A major portion of the PGE mineralisation is associated with BMS as is indicated by the ‘moderate’ (Overysel r = +0.62) to ‘very good’ (Sandsloot r = +0.79) PPGE-S bulk-rock correlation, whereas an excellent PPGE-Ni correlation (especially at Overysel) indicates that pentlandite is a major PGE- carrier. These results are corroborated by the trace element contents of the BMS and by mass balance calculations. For instance, the LA-ICP-MS BMS study revealed average concentrations of 65 to 165 ppm Pd and 0.17 to 13 ppm Rh at Overysel, and 156 to 412 ppm Pd and 18 to 57 ppm Rh at Sandsloot in pentlandite of both the mineralized pyroxenites. In contrast, chalcopyrite and pyrrhotite are almost devoid of PGE. Platinum and the IPGE (Ir, Os, Ru) are very low in the BMS and, therefore, are thought to be hosted in discrete PGM grains. This conclusion is supported by the mass balance calculations for Pt and by the actual presence of PGM grains in both sample suites. The presence of discrete PGM grains explains the calculated gap between the whole-rock PPGE concentrations and the PPGE concentration in the mineral phases as revealed by the mass balance calculations. The PPGE concentrations in the BMS and the complementary mass balance calculations are in general agreement with those of the Merensky Reef and the UG-2, in both of which large proportions of the whole-rock Pd and Rh are hosted by pentlandite, whereas Pt and the IPGE mainly occur in discrete PGM rather than being hosted by BMS. However, comparison of our results with those of the Merensky Reef and the UG-2 indicates that the average maximum Pd and Rh concentrations in pentlandite are distinctly lower in the Platree
Keywords: Africa; base metals; Bushveld Complex; copper ores; geochemical methods; ICP mass spectra; igneous rocks; Malmani Subgroup; mass spectra; metal ores; metals; mineral exploration; nickel ores; platinum group; platinum ores; plutonic rocks; pyroxenite; South Africa; Southern Africa; spectra; sulfides; ultramafics; whole rock; Sandsloot Mine; Mogalakwena Mine; Platreef Mine